(untitled) (International Journal of Engineering and Computer Science, 2025)
This study examines the transition from monolithic applications to a microservices architecture and its impact on the scalability and performance of corporate information systems. A comparative analysis is conducted based on scientific publications and practical experiments, highlighting key parameters such as latency under peak loads, resource consumption in high-concurrency environments, and challenges in ensuring data consistency. Special attention is given to DevOps practices, including test automation, distributed service monitoring, and continuous integration. Methodological aspects are also considered, including Agile approaches (Scrum, Kanban), event-driven messaging (RabbitMQ, Kafka), and container orchestration tools (Docker, Kubernetes), which facilitate structured updates and rapid failure response. The analysis confirms that microservices enhance the flexibility of feature deployment and reduce the risk of complete system downtime. However, they require significant efforts in planning, centralized logging, and architectural standardization. This study will be of interest to project managers, architects, developers, and researchers focused on optimizing distributed applications.